Incidence and outcomes of neonatal acute kidney injury (AWAKEN): a multicentre, multinational, observational cohort study. (November 2017) - Jetton, Jennifer G; Boohaker, Louis J; Sethi, Sidharth K; Wazir, Sanjay; Rohatgi, Smriti; Soranno, Danielle E; Chishti, Aftab S; Woroniecki, Robert; Mammen, Cherry; Swanson, Jonathan R; Sridhar, Shanthy; Wong, Craig S; et al.
Summary: Background: Findings from single-centre studies suggest that neonatal acute kidney injury (AKI) is associated with poor outcomes. However, because of the small sample size of those studies, few inferences can been made regarding the independent associations between AKI, mortality, and hospital length of stay. We aimed to establish whether neonatal AKI is independently associated with increased mortality and length of hospital stay. Methods: We did this multicentre, multinational, retrospective cohort study of critically ill neonates admitted to 24 participating neonatal intensive care units (NICUs) in four countries (Australia, Canada, India, USA) between Jan 1 and March 31, 2014. We included infants born or admitted to a level 2 or 3 NICU and those who received intravenous fluids for at least 48 h. Exclusion criteria were admission at age 14 days or older, congenital heart disease requiring surgical repair within 7 days of life, lethal chromosomal anomaly, death within 48 h of admission, inability to determine AKI status, or severe congenital kidney abnormalities. We defined AKI as an increase in serum creatinine of 0·3 mg/dL or more (≥26·5 μmol/L) or 50% or more from the previous lowest value, or a urinary output of less than 1 mL/kg per h on postnatal days 2–7. We used logistic regression to calculate crude odds ratios (ORs) and associated 95% CIs for the association between AKI and likelihood of death. We used linear regression to calculate the crude parameter estimates and associated 95% CIs for the association between AKI and length of hospital stay. Multivariable logistic and linear regression models were run to account for potential confounding variables. We additionally created regression models stratified by gestational age groups (22 weeks to <29 weeks, 29 weeks to <36 weeks, and ≥36 weeks). This study is registered withClinicalTrials.gov, numberNCT02443389 . Findings: We enrolled 2162 infants, of whom 2022 (94%) had data to ascertain AKI status. 605 (30%) infants had AKI. Incidence of AKI varied by gestational age group, occurring in 131 (48%) of 273 of patients born at 22 weeks to less than 29 weeks, 168 (18%) of 916 patients born at 29 weeks to less than 36 weeks, and 306 (37%) of 833 patients born at 36 weeks or older. Infants with AKI had higher mortality than those without AKI (59 [10%] of 605 vs 20 [1%] of 1417 infants; p<0·0001), and longer length of hospital stay (median 23 days [IQR 10–61] vs 19 days [9–36]; p<0·0001). These findings were confirmed in both crude analysis of mortality (OR 7·5, 95% CI 4·5–12·7; p<0·0001 for AKI vs no AKI) and length of stay (parameter estimate 14·9 days, 95% CI 11·6–18·1; p<0·0001) and analysis adjusted for multiple confounding factors (adjusted OR 4·6, 95% CI 2·5–8·3; p<0·0001 and adjusted parameter estimate 8·8 days, 95% CI 6·1–11·5; p<0·0001, respectively). Interpretation: Neonatal AKI is a common and independent risk factor for mortality and increased length of hospital stay. These data suggest that AKI might have a similar effect in neonates as in paediatric and adult patients. Strategies designed to prevent AKI and treatments to reduce the burden of AKI, including renal support devices designed for neonates, are greatly needed to improve the outcomes of these vulnerable infants. Funding: US National Institutes of Health, University of Alabama at Birmingham, Cincinnati Children's Hospital, University of New Mexico, Canberra Hospital Private Practice fund, and 100 Women Who Care.